Serum sialic acid levels in health and disease - Carter, Ann (1962)
Sialic acid levels in normal and pathological sera estimated by the improved Svennerholm technique are reported. The increased levels demonstrable in rheumatoid arthritis, cirrhosis, γ myelomata, and macroglobulinaemia are demonstrated as being explicable on the basis of increased production of proteins of normal sialic content. Tentative reasons are given for the possibility that abnormal binding of sialic acid may occur in nephrotic sera and sera from β globulin myelomata. The latter may be confused with `macroglobulinaemia'.